Cleavage and degradation of EDEM1 promotes coxsackievirus B3 replication via ATF6a‐mediated unfolded protein response signalling. (9th March 2020) - Zhang, Huifang M.; Qiu, Ye; Zhao, Guangze; Wang, Hua; Chen, Yankuan T.; Aghakeshmiri, Sana; Hanson, Paul; Yang, Decheng
Abstract: Our previous study of coxsackievirus B3 (CVB3)‐induced unfolded protein responses (UPR) found that overexpression of ATF6a enhances CVB3 VP1 capsid protein production and increases viral particle formation. These findings implicate that ATF6a signalling benefits CVB3 replication. However, the mechanism by which ATF6a signalling is transduced to promote virus replication is unclear. In this study, using a Tet‐On inducible ATF6a HeLa cell line, we found that ATF6a signalling downregulated the protein expression of the endoplasmic reticulum (ER) degradation‐enhancing α‐mannosidase‐like protein 1 (EDEM1), resulting in accumulation of CVB3 VP1 protein; in contrast, expression of a dominant negative ATF6a had the opposite effect. Furthermore, we found that EDEM1 was cleaved by both CVB3 protease 3C and virus‐activated caspase and subsequently degraded via the ubiquitin‐proteasome pathway. However, overexpression of EDEM1 caused VP1 degradation, likely via a glycosylation‐independent and ubiquitin‐lysosome pathway. Finally, we demonstrated that CRISPR/Cas9‐mediated knockout of EDEM1 increased VP1 accumulation and thus CVB3 replication. This is the first study to report the ER protein quality control of non‐enveloped RNA virus and reveals a novel mechanism by which CVB3 evades host ER quality control pathways through cleavage and degradation of the UPR target gene EDEM1, to ultimately benefit its own replication.